2017
DOI: 10.1159/000485318
|View full text |Cite
|
Sign up to set email alerts
|

Intralenticular Ozurdex® – One Year Later

Abstract: Reported here is a case of intralenticular sustained-release dexamethasone implant (Ozurdex®, Allergan, Irvine, CA, USA) present for 1 year with effective treatment of refractory diabetic macular edema without rapid cataract formation. The crystalline lens remained stable for 12 months on exam despite the presence of the steroid-secreting foreign body. The diabetic macular edema resolved on exam and on optical coherence tomography. After 1 year, cataract extraction was uneventfully performed by phacoemulsifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…ere are some conflicting studies that reported no cataract progression even after accidental intralenticular Ozurdex implant administration [24,25]. In addition, many authors have revealed a resolution of the ME with an intralenticular implant [24,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…ere are some conflicting studies that reported no cataract progression even after accidental intralenticular Ozurdex implant administration [24,25]. In addition, many authors have revealed a resolution of the ME with an intralenticular implant [24,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal position of the implant does not affect the efficacy of the implant, as has been demonstrated in cases of intralenticular placement of the implant even with a cataract formation 1 3. Anterior chamber migration is more sinister as it may potentially lead to corneal decompensation 5.…”
Section: Discussionmentioning
confidence: 91%
“…Management of complication from cases, arising out of intralenticular placement of Ozurdex with or without cataract formation has been described 1–3. Spontaneous migration, of an Ozurdex implant into the anterior chamber in the presence of anterior chamber implant has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated cataract development has been reported in some intralenticular Ozurdex implant administration cases [46], while other cases had increased IOP [8] or both these complications together [9, 10]. Poornachandra et al [11] and Clemente-Tomás et al [3] have reported no acceleration of cataract progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have also been increasing reports of accidental injection of Ozurdex into the crystalline lens [313]. Some authors feel expectant waiting is better [3, 4, 7, 10, 11] while others suggest immediate phacoemulsification (PE) for the cataract [5, 6, 13].…”
Section: Introductionmentioning
confidence: 99%